Bezold–Jarisch reflex-mediated asystole during dobutamine stress testing: a case report. Issue 6 (15th November 2020) - Hossain, Nimrah; Hossain, Naseem; Al-Sadawi, Mohammed; Haq, Salman
Abstract: Background: The Bezold–Jarisch reflex (BJR) is a cardioinhibitory parasympathetic response to activation of ventricular mechanoreceptors, which can result in bradycardia, atrioventricular block, or asystole. This phenomenon has been triggered by acute myocardial ischaemia, intra-arterial nitroglycerine use, natriuretic peptides, and with exceptional rarity, in middle-aged women only, by dobutamine infusion during stress echocardiography. Case summary: We present the case of a 61-year-old woman who suffered a 5.1-s sinus pause during her 20 μg/kg/min infusion of dobutamine. Recovery was immediate following termination of dobutamine infusion. Concurrent echocardiography was normal, and subsequent cardiac catheterization and electrophysiologic study were normal. Discussion: This is the fifth documented case of a severe BJR causing asystole during dobutamine infusion, which adds to the accumulating evidence supporting the benign nature of the condition.